2015
DOI: 10.1073/pnas.1418163112
|View full text |Cite
|
Sign up to set email alerts
|

BRAF inhibitor resistance mediated by the AKT pathway in an oncogenic BRAF mouse melanoma model

Abstract: BRAF (v-raf murine sarcoma viral oncogene homolog B) inhibitors elicit a transient anti-tumor response in ∼80% of BRAF V600 -mutant melanoma patients that almost uniformly precedes the emergence of resistance. Here we used a mouse model of melanoma in which melanocyte-specific expression of Braf V618E (analogous to the human BRAF V600E mutation) led to the development of skin hyperpigmentation and nevi, as well as melanoma formation with incomplete penetrance. Sleeping Beauty insertional mutagenesis in this mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
133
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(141 citation statements)
references
References 67 publications
8
133
0
Order By: Relevance
“…Importantly, our findings were confirmed in patient-derived xenograft models, underlining the benefit of large-scale in vivo forward genetic screening to identify potential resistance mechanisms to targeted therapeutics. (20). Consequently, we conducted a large-scale transposon-based insertional mutagenesis screen to investigate the resistance to HDM201 in mice.…”
Section: Significancementioning
confidence: 99%
“…Importantly, our findings were confirmed in patient-derived xenograft models, underlining the benefit of large-scale in vivo forward genetic screening to identify potential resistance mechanisms to targeted therapeutics. (20). Consequently, we conducted a large-scale transposon-based insertional mutagenesis screen to investigate the resistance to HDM201 in mice.…”
Section: Significancementioning
confidence: 99%
“…Additionally, studies with the combination of vemurafenib and the MEK inhibitor selumetinib showed that combination with different PI3K pathway inhibitors led to synergistic reduction of cell viability and enhanced apoptosis in vitro (18). Perna et al (19) also observed that in a mouse model of BRAF mutant melanoma, hyperphosphorylation of AKT conferred resistance to vemurafenib and this resistance could be reversed by combinatorial treatment with both vemurafenib and an AKT inhibitor. However, a better understanding of the mechanism of how and when NRAS isoform 2 binds to RAF and PI3K could serve to elucidate additional treatment strategies.…”
Section: Discussionmentioning
confidence: 96%
“…They treated Tyrosinase-Cre ERT2 ; Rosa26-LSL-SB13; T2/Onc; LSL-Braf V618E/+ mice displaying melanomas with the BRAF inhibitor PLX4720, and identified ERas as a novel candidate that mediates resistance to PLX4720 [22 ]. This study shows that insertional mutagenesis can be also used for the identification of molecular mechanisms involved in drug resistance.…”
Section: Box 1 Sleeping Beauty and Piggybac Featuresmentioning
confidence: 94%